PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS PENGGUNA KASMDI KBS - Prakosa, Galih Arief; Ciptomulyono, Udisubakti; Achmadi, Fuad (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: The availability of consumable water is a basic human right. The State Water Supply Company (PDAM) Surya Sembada is the only government institution in charge in providing and managing drinking water facilities and infrastructure in Surabaya. PDAM Surya Sembada provides free fountain drinking (KASM) as their Corporate Social Responsibility (CSR) program that located in various strategic public places in the city including in Surabaya Zoo (KBS). However, there has never been any analysis on the product and service quality of the KASM in KBS. Therefore, the objective of this study is to analyze the effect of product and service quality of the KASM in KBS on user satisfaction and loyalty using Structural Equation Modeling (SEM) with Partial Least Square (PLS) analysis. Results of path coefficient analysis show that product quality affects user satisfaction, but it has no effect on user loyalty. Service quality affects user satisfaction and loyalty. User satisfaction affects user loyalty. It can be concluded that user satisfaction is affected by product and service quality, while user loyalty is affected by service quality and user satisfaction. Keywords: KASM, Product Quality, Service Quality, User Satisfaction, User Loyalty.